Study of the production system of coffee (Coffea arabica L.) in the Frailesca region, Chiapas - Ruiz-Nájera, Ramiro Eleazar (Universidad Autónoma de Tamaulipas, 2016)
Coffee growing areas in the Mexican state of Chiapas are characterized by their environmental, technical, economic and sociocultural contrasts. In particular, there is a need to improve the low production levels of many of these farms. The objective of this study was to analyze the participation of different actor’s (Coffea arabica L.), in the environmental and socioeconomic aspects of the coffee production system in the Frailesca region, in central Chiapas. Toward this objective, 243 questionnaires were administered to farmers who grow coffee. We identified a need to promote technification of the coffee growing process and to improve the following conditions: lack of infrastructure for processing the coffee, poor plantation management, lack of farmer organization to obtain credit, lack of technical support for the transformation of conventional coffee production into organic one, soil conservation, and water management in wet processing. This study reviews the difficulties in increasing the profitability of the crop, and makes suggestions regarding planning the management process of the coffee production system in order to satisfy market demands with respect to quality and food safety. Archive XML (SciELO)